Fast computation of dissipative quantum systems with ensemble rank truncation - McCaul, Gerard; Jacobs, Kurt; Bondar, Denys I. (Physical review research, 2021)
We introduce a new technique for the simulation of dissipative quantum systems. This method is composed of an approximate decomposition of the Lindblad equation into a Kraus map, from which one can define an ensemble of wave functions. Using principal component analysis, this ensemble can be truncated to a manageable size without sacrificing numerical accuracy. We term this method ensemble rank truncation (ERT), and find that in the regime of weak coupling, this method is able to outperform existing wave-function Monte Carlo methods by an order of magnitude in both accuracy and speed. We also explore the possibility of combining ERT with approximate techniques for simulating large systems [such as matrix product states (MPS)], and show that in many cases this approach will be more efficient than directly expressing the density matrix in its MPS form. We expect the ERT technique to be of practical interest when simulating dissipative systems for quantum information, metrology, and thermodynamics.